A Legal Appraisal of the Challenges Faced by Forwarding Agents in Cameroon - Kum, Felix Fung (Law and Economy, 2025)
Forwarding agents play a crucial role in facilitating international trade by managing the logistics and documentation necessary for the smooth transit of goods. In Cameroon, a rapidly growing economy with increasing trade activities, forwarding agents are pivotal in ensuring efficiency and compliance in supply chains. Despite their importance, forwarding agents in Cameroon face numerous challenges that hinder their operational efficiency and affect the overall trade environment. These challenges include bureaucratic delays, inadequate infrastructure, regulatory complexities, and security issues, which collectively impact on their performance and the country’s trade competitiveness. This article aims to appraise the key challenges faced by forwarding agents in Cameroon. The research adopts the qualitative research methodology, and data were obtained from books, article Journals. The study reveals that forwarding agents predominantly struggle with cumbersome customs procedures, poor transport infrastructure, inconsistent regulatory frameworks, and security threats such as cargo theft. These challenges result in increased operational costs, delays in shipment processing, and reduced competitiveness in the logistics sector. It is recommended that there is the need to streamline and simplify customs clearance procedures to reduce delays and bureaucratic hurdles at ports, particularly Douala, which faces congestion and long cargo dwell times.